Deadly and venomous Lonomia caterpillars are more than the two usual suspects - Camila González; Liliana Ballesteros-Mejia; Juana Díaz-Díaz; Diana M. Toro-Vargas; Angela R. Amarillo-Suarez; Delphine Gey; Cielo León; Eduardo Tovar; Mónica Arias; Nazario Rivera; Luz Stella Buitrago; Roberto H. Pinto-Moraes; et al. (Public Library of Science (PLoS), 2023)
Caterpillars of the Neotropical genus Lonomia (Lepidoptera: Saturniidae) are responsible for some fatal envenomation of humans in South America inducing hemostatic disturbances in patients upon skin contact with the caterpillars' spines. Currently, only two species have been reported to cause hemorrhagic syndromes in humans: Lonomia achelous and Lonomia obliqua. However, species identifications have remained largely unchallenged despite improved knowledge of venom diversity and growing evidence that the taxonomy used over past decades misrepresents and underestimates species diversity. Here, we revisit the taxonomic diversity and distribution of Lonomia species using the most extensive dataset assembled to date, combining DNA barcodes, morphological comparisons, and geographical information. Considering new evidence for seven undescribed species as well as three newly proposed nomenclatural changes, our integrative approach leads to the recognition of 60 species, of which seven are known or strongly suspected to cause severe envenomation in humans. From a newly compiled synthesis of epidemiological data, we also examine the consequences of our results for understanding Lonomia envenomation risks and call for further investigations of other species' venom activities. This is required and necessary to improve alertness in areas at risk, and to define adequate treatment strategies for envenomed patients, including performing species identification and assessing the efficacy of anti-Lonomia serums against a broader diversity of species. Author summary Caterpillars of the genus Lonomia (Lepidoptera: Saturniidae) are responsible for some fatal envenomation of humans in South America due to the hemotoxic activity of their venom. Historically, only two species have been reported to cause such hemorrhagic syndromes in humans, Lonomia achelous and Lonomia obliqua; however, the number of species described in the last decade within the genus has increased by 300% indicating that the diversity of the genus has been underestimated. Here, we revise some taxonomic aspects of genus Lonomia, update the diversity and their spatial distribution, and highlight their potential epidemiological relevance. We provide evidence of seven species being potentially involved in accidents and at least three undescribed new species. Our work emphasizes the need for further research of Lonomia as a genus with medical importance.